Impact of a preceding radiotherapy on the outcome of immune checkpoint inhibition in metastatic melanoma: a multicenter retrospective cohort study of the DeCOG - Dirk Schadendorf; Carola Berking; Lucie Heinzerling; Lisa Zimmer; Ralf Gutzmer; Alexander Kreuter; Andreas Stang; Elisabeth Livingstone; Benjamin Weide; Eleftheria Chorti; Selma Ugurel; Anja Gesierich; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibition (ICI) is an essential treatment option in melanoma. Its outcome may be improved by a preceding radiation of metastases. This study aimed to investigate the impact of a preceding radiotherapy on the clinical outcome of ICI treatment.Methods This multicenter retrospective cohort study included patients who received anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) or anti-programmed cell death protein 1 (PD-1) ICI with or without preceding radiotherapy for unresectable metastatic melanoma. ICI therapy outcome was measured as best overall response (BOR), progression-free (PFS) and overall survival (OS). Response and survival analyses were adjusted for confounders identified by directed acyclic graphs. Adjusted survival curves were calculated using inverse probability treatment weighting.Results 835 patients who received ICI (anti-CTLA-4, n=596; anti-PD-1, n=239) at 16 centers were analyzed, whereof 235 received a preceding radiotherapy of metastatic lesions in stage IV disease. The most frequent organ sites irradiated prior to ICI therapy were brain (51.1%), lymph nodes (17.9%) and bone (17.9%). After multivariable adjustment for confounders, no relevant differences in ICI therapy outcome were observed between cohorts with and without preceding radiotherapy. BOR was 8.7% vs 13.0% for anti-CTLA-4 (adjusted relative risk (RR)=1.47; 95% CI=0.81 to 2.65; p=0.20), and 16.5% vs 25.3% for anti-PD-1 (RR=0.93; 95% CI=0.49 to 1.77; p=0.82). Survival probabilities were similar for cohorts with and without preceding radiotherapy, for anti-CTLA-4 (PFS, adjusted HR=1.02, 95% CI=0.86 to 1.25, p=0.74; OS, HR=1.08, 95% CI=0.81 to 1.44, p=0.61) and for anti-PD-1 (PFS, HR=0.84, 95% CI=0.57 to 1.26, p=0.41; OS, HR=0.73, 95% CI=0.43 to 1.25, p=0.26). Patients who received radiation last before ICI (n=137) revealed no better survival than those who had one or more treatment lines between radiation and start of ICI (n=86). In 223 patients with brain metastases, we found no relevant survival differences on ICI with and without preceding radiotherapy.Conclusions This study detected no evidence for a relevant favorable impact of a preceding radiotherapy on anti-CTLA-4 or anti-PD-1 ICI treatment outcome in metastatic melanoma.